Penerapan Model Discovery Learning Berbantu Media Spinning Wheel dalam Pembelajaran Menelaah Teks Serat Wedhatama Pupuh Pangkur Siswa Kelas X Kuliner 1 SMK Mataram Semarang Tahun 2022/2023 - Safitri, Ima Yulia; Sunarya, Sunarya; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2025)
The background of this research is the lack of students' interest in the text of Serat Wedhatama Pupuh Pangkur which only contains chapters and complete sentences. Thus, the formulation of the problem can be formed as a result of applying the discovery learning model assisted by the rotating wheel media in Wedhatama's fibrous text repetition learning. Pupuh Pangkur for class X students of Mataram Mataram Vocational School in the 2022 academic year/2023 academic year. The purpose of this study was to describe the results of applying the Spinning Wh eel in learning and studying the text of Wedhatama Pupuh Pangkur. This research includes descriptive quantitative research, because the data obtained is calculated in a quantitative descriptive manner by presenting the results of data calculations. The source of this research data is the results of student scores in learning the Wedhatama Pupuh Pangkur fiber text. The technique used for data collection is testing and testing techniques. Sampling in this study using a purposive sampling technique. Based on the data analysis above, the results of this study can be stated: 1) Class X Culinary 1 does not use a Spinning Wheel, so students get bored easily when distributing material. 2) In Class X Culinary 1 using the Spinning Wheel, students tend to be enthusiastic and focus on the material presented.